The Effectiveness of Safety Flour Clay Therapy on Fine Motor Skills of Children with Autism - Puspita, Sindi Rosy; Hardini, Deisy Sri (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Data from the World Health Organization indicate a high prevalence of autism-related disabilities, with many children experiencing developmental delays of over five years and limited fine motor skills typically seen at the level of children aged 3 to 4. This study aims to support children with autism by enhancing their fine motor development through Safety Flour Clay therapy. The research was conducted to examine the effect of this therapy on improving fine motor skills in children with autism at SLB C and C1 Yakut Purwokerto and SLB Negeri Banjarnegara. A quantitative approach was employed using a pre-experimental design with a one-group pretest-posttest format without a control group. A total of 30 participants were selected through total sampling. Data were collected through observation using standardized instruments and analyzed with the Wilcoxon Signed Ranks Test. The results showed a significance value of 0.000 (p < 0.05), indicating a significant effect of Safety Flour Clay therapy on the improvement of fine motor skills in children with autism. This therapy presents a promising alternative to support physical development, particularly in the area of fine motor coordination.